2007
DOI: 10.1002/dneu.20540
|View full text |Cite
|
Sign up to set email alerts
|

Laminin and fibronectin modulate inner ear spiral ganglion neurite outgrowth in an in vitro alternate choice assay

Abstract: Extracellular matrix (ECM) molecules have been shown to function as cues for neurite guidance in various populations of neurons. Here we show that laminin (LN) and fibronectin (FN) presented in stripe micro-patterns can provide guidance cues to neonatal (P5) inner ear spiral ganglion (SG) neurites. The response to both ECM molecules was dose-dependent. In a LN versus poly-L-lysine (PLL) assay, neurites were more often observed on PLL at low coating concentrations (5 and 10 microg/mL), while they were more ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 21 publications
3
42
1
Order By: Relevance
“…A dose-dependent effect of these ECM proteins has also been found in studies using micropatterned substrates. When PLL is used as background substrate (through precoating), neurite preference for LN is observed only at rather high LN concentrations, whereas in case of direct competition between LN and FN, neurites prefer LN, independently of the concentration of LN [Gundersen 1987;Evans et al, 2007]. In this study, we also noticed such dose-dependent effects (data not shown).…”
Section: Affinity Of Growth Cone Receptors For Ln and Fn Ligandscontrasting
confidence: 42%
See 1 more Smart Citation
“…A dose-dependent effect of these ECM proteins has also been found in studies using micropatterned substrates. When PLL is used as background substrate (through precoating), neurite preference for LN is observed only at rather high LN concentrations, whereas in case of direct competition between LN and FN, neurites prefer LN, independently of the concentration of LN [Gundersen 1987;Evans et al, 2007]. In this study, we also noticed such dose-dependent effects (data not shown).…”
Section: Affinity Of Growth Cone Receptors For Ln and Fn Ligandscontrasting
confidence: 42%
“…Several molecular substrate micropatterning techniques, such as lithography and lCP, have been developed as a means to investigate cellular processes such as proliferation, apoptosis, morphogenesis, differentiation and neurite outgrowth [Gundersen, 1987;Clark et al, 1993;Gomez and Letourneau, 1994;Kuhn et al, 1995;Gomez et al, 1996;Tai and Buettner, 1998;Renaudin et al, 1999;Wheeler et al, 1999;Corey and Feldman, 2003;Adams et al, 2005;Turney and Bridgman, 2005;Thery et al, 2006;Evans et al, 2007;Fink et al, 2007]. This study illustrates the efficacy and versatility of micropatterned substrates to analyze the molecular interactions underlying the point-to-point navigation of individual growth cones.…”
Section: The Micropatterned Substratesmentioning
confidence: 89%
“…Regrowth of SGN peripheral axons toward the stimulating electrodes might allow reduced currents, more refined stimulation paradigms, and improved functional outcomes (Rubinstein, 2004). Thus, there is growing interest in therapeutic strategies to induce regrowth of SGN peripheral processes towards a stimulating electrode (Bianchi and Raz, 2004, Roehm and Hansen, 2005, Wittig et al, 2005, Evans et al, 2007. To the extent that chronic depolarization mimics electrical stimulation in vivo (Hegarty et al, 1997, Miller et al, 2003, inhibition of neurite outgrowth by depolarization suggests an additional consideration in the development of such strategies.…”
Section: Implications For Cochlear Implant Technologymentioning
confidence: 99%
“…neurites among the dissociated SGN cultures. There were often Schwann cells and fibroblasts surrounding the neurites (data not shown), which could not only be obstacles to the migration of a growth cone, but could also act as guidance cues to neurites (Evans et al, 2007). Furthermore, the digesting procedure for the preparation of dissociated cultures may destroy membranous proteins, which are essential to neurite guidance.…”
Section: Sgn Culturing and Imaging System With The Application Of Efsmentioning
confidence: 96%